If x is not equal to zero, and x = sqrt(4xy-4y^2), then in terms of y, x =
Theres an alternative to straight algebra.
Plug in 2 for y. We eventually get x^2-8x+16=0 (x-4)(x-4)=0
so x=4. Since y =2 2y=4=x.
Now this method isnt full proof as other answer choices may yield the same result. E could be a candidate b/c -2*-2=4. So try -2 in the equation for y. It turns out its not the same.
I only use this when for some reason I can't figure out how to factor something etc.. Id suggest tryin algebra first.